Comparison of house dust mite sensitization profiles in allergic adults from Canada, Europe, South Africa and USA. Issue 7 (6th March 2021) - Muddaluru, Varun; Valenta, Rudolf; Vrtala, Susanne; Schlederer, Thomas; Hindley, James; Hickey, Pascal; Larché, Mark; Tonti, Elena
Abstract: Background: Sensitization to house dust mite (HDM) is a leading cause of allergic rhinitis and asthma. Despite more than 30 HDM‐derived allergens having been identified to date, specific therapeutic approaches do not yet take into account the local sensitization profiles of patients. This study aimed to identify patterns of HDM sensitization in HDM‐allergic adults living in distinct geographic areas, to inform the development of targeted diagnostic and therapeutic tools. Methods: Serum samples from 685 HDM‐allergic subjects from Canada, Europe, South Africa, and the USA were tested for levels of IgE specific for 17 micro‐arrayed HDM allergens by ImmunoCAP Immuno Solid‐phase Allergen Chip (ISAC) technology. Results: The results confirmed significant geographical variability in sensitization patterns and levels of IgE. In all areas, the major sensitizers were the group 1 and group 2 allergens and Der p 23. Der p 23 was a frequent sensitizer: 64% of the subjects had IgE specific for Der p 23, and 2.3% were monosensitized to it. In South Africa, Der p 23 was the dominant HDM allergen (86% prevalence) and Der p 7 achieved major allergen status (56%). IgE sensitization to HDM was influenced by asthmatic status, levels of allergen exposure, age, race‐ethnicity and smoking status, but not by BMI. Conclusion: Sensitization profiles to HDM allergens differ considerably among distinct geographic areas, with Der p 7 and Der p 23 being major sensitizers in South Africa. Such heterogeneity should be taken into account in the diagnosis and treatment of HDM‐allergic patients. Abstract : Immunoglobulin E sensitization to major house dust mite allergens varies by geographic region. Der p 23 is the dominant house dust mite allergen in South Africa. Der p 7 is a major allergen in South Africa.